Pt/Mg-Ce-O catalyst for NO/H2/O2 lean de-No x reaction - Costa, Costas; Efstathiou, A. M. (My University, 2004)
The NO/H2/O2 reaction was studied under oxidizing conditions in the 100-400 °C range over 0.1 wt% Pt supported on various metal oxides such as MgO, CeO2, SiO2, La2O3, CaO, Y2O3 and TiO2. The Pt/MgO and Pt/CeO2 catalysts showed good catalytic behaviours. Here, we find that the Pt/Mg-Ce-O catalyst, prepared from MgO and CeO2 by the sol-gel method, is a very active and selective catalyst towards N2 formation in the whole 100–400 °C range. This catalyst appears to be the most active, selective and stable one ever reported in the literature for the NO/H2/O2 reaction, even in the presence of 5%v H2O or 20 ppmv of SO2 in the feed stream.
Keywords: Lean de-NOx; NO reduction; Supported platinum; Mixed metal oxides